An ATP-stabilized inhibitor of the proteasome is a component of the 1500-kDa ubiquitin conjugate-degrading complex. - Driscoll, J (1992)
Proteins conjugated to ubiquitin are degraded by a 26S (1500-kDa) proteolytic complex that, in reticulocyte extracts, can be formed by the association of three factors: CF-1, CF-2, and CF-3. One of these factors, CF-3, has been shown to be the proteasome, a 650-kDa multicatalytic protease complex. We have purified a 250-kDa inhibitor of the proteasome and shown that it corresponds to CF-2. In the presence or absence of ATP, this factor inhibited hydrolysis by the proteasome of both fluorogenic tetrapeptides and protein substrates. When the inhibitor, proteasome, and CF-1 were incubated together in the presence of ATP and Mg2+, degradation of ubiquitin-125I-lysozyme occurred. Both the inhibitory activity and the ability to reconstitute ubiquitin-125I-lysozyme degradation were very labile at 42 degrees C, but both activities were stabilized by ATP or a nonhydrolyzable ATP analog. SDS/PAGE indicated that the 250-kDa inhibitor fraction contained a major subunit of 40 kDa (plus some minor bands). The 125I-labeled inhibitor and purified proteasome formed a complex. When CF-1, ATP, and Mg2+ were also present, the 125I-labeled inhibitor along with the proteasome formed a complex of 1500 kDa. The inhibitor (CF-2) thus appears to be an ATP-binding component that regulates proteolysis within the 1500-kDa complex.